Environmental Concern and Individual Innovation on Halal Green Skincare Purchase Intention - Alam, Azhar; Utami, Dwi; Hakim, Lukmanul; Karima, Nida Izzatul; Ullah, Ihtisham (International Review of Management and Marketing, 2025)
This study investigates the influence of environmental concern and individual innovation on the intention to purchase halal green skincare products, with halal product knowledge as a moderating variable. Using Structural Equation Modeling with Partial Least Squares (SEM-PLS), data from 220 Indonesian respondents were analyzed. The results reveal that environmental concern, individual innovation, and halal product knowledge significantly and positively affect the intention to purchase halal green skincare products. However, halal product knowledge does not considerably moderate the relationships between environmental concern or individual innovation and purchase intention. The study’s focus on Indonesian consumers and halal green skincare products may limit its generalizability. These findings suggest marketers should emphasize environmental benefits, innovative features, and halal certification to increase consumer purchase intention. By integrating environmental concern, individual innovation, and halal product knowledge in the context of green skincare products, this research provides valuable insights into the factors influencing Muslim consumers’ purchase intentions for environmentally friendly and halal-certified skincare products.